Non-coding RNA Activated by DNA Damage: Review of Its Roles in the Carcinogenesis - Ghafouri-Fard, Soudeh; Azimi, Tahereh; Hussen, Bashdar Mahmud; Abak, Atefe; Taheri, Mohammad; Dilmaghani, Nader Akbari (Frontiers in Cell and Developmental Biology, 2021)
Long intergenic non-coding RNA 00657 (LINC00657) or “noncoding RNA activated by DNA damage” (NORAD) is an extremely conserved and copious long non-coding RNA (lncRNA). This transcript has pivotal role in the preservation of genome integrity. Several researches have appraised the role of NORAD in the evolution of human cancers with most of them indicating an oncogenic role for this lncRNA. Several miRNAs such as miR-199a-3p, miR-608, miR‐155‐5p, miR-590-3p, miR-495-3p, miR-608, miR-202-5p, miR-125a-3p, miR-144-3p, miR‐202‐5p and miR-30a-5p have been recognized as targets of NORAD in different cancer cell lines. In addition, NORAD has interactions with cancer-related pathways, particularly STAT, TGF-β, Akt/mTOR and PI3K/AKT pathway. Over-expression of NORAD has been related with poor clinical outcome of patients with diverse types of neoplasms. Collectively, NORAD is a prospective marker and target for combating cancer.